Educational and cultural aspects of the activities of sports associations in Poland in the interwar period - Piotr Kędzia (Kazimierz Wielki University, 2020)
Sports associations in the interwar period were active in many areas of social life. One of the basic goals they pursued was the training of players who taking active part in various competitions and sports competitions,  fought for the highest positions and trophies. However, there were also such organizations whose work went beyond sports competition, focusing also on multidirectional educational and cultural activities. These associations, through special sections, as well as various forms of non-sport activities organized a series of self-education, training, artistic and tourist activities et al. The implementation of these activities, both in the field of sport, as well as in the field of culture and education, raised the prestige of associations among the local community, expanded their leisure activities, liberated social instincts and created a kind of myth [5, p. 127]. Thanks to such initiatives, members expanded their knowledge, developed skills and interests, and as a consequence became more enlightened and conscious citizens-athletes. This diversity of socio-cultural impact also had a direct impact on the formation of personality. Sports organizations as educational environments shaped the character of young sport adepts, shaping prosocial, pro-health and prosomatic attitudes.